(untitled) (Colombia Medica, 2006)
The preventive guides are condensations of the different interventions in health promotion and disease prevention that are made to take part of the population’s interventions. They contain council strategies, screening and specific measures of protection. It is mentioned the characteristics of screening test. It presents the preventive guides by each individual vital cycle as far as council measures, specific protection and screening. Thus, a concrete guide offers itself on the interventions to carry out preventive consultations with the patients in Colombia.